2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8036817
|View full text |Cite
|
Sign up to set email alerts
|

Design of focal brain cooling system for suppressing epileptic seizures

Abstract: Epilepsy is a group of diseases caused by excessive neuronal activities, and one-quarter of the patients do not become seizure-free by the existing treatments. The potential treatments include focal brain cooling, which aims to cool the region where the excessive neuronal activities begin. We are developing a focal brain cooling system. The system delivers cold saline to a cranially implanted cooling device. The outflow is cooled by a Peltier device and pumped for circulation. The Peltier device and the pump a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is well known that hypothermia around 32-34°C helps protect the brain in patients experiencing postcardiac arrest 12 or severe neurotrauma [13][14][15][16] through the suppression of brain metabolism 17 and glutamate release. 18 We found that epileptic seizures terminated at 15°C or lower [19][20][21][22][23][24][25][26][27][28] and found that neuronal function deteriorated at 10°C or lower. 29,30 The threshold of low temperature for histological brain damage is not known exactly; however, irreversible damage occurred neither by continuous cooling at 5°C for 1 hour 31 nor by cooling in repeats of 30 sec at 5°C with a 1.5-min interval for 2 hours.…”
mentioning
confidence: 85%
“…It is well known that hypothermia around 32-34°C helps protect the brain in patients experiencing postcardiac arrest 12 or severe neurotrauma [13][14][15][16] through the suppression of brain metabolism 17 and glutamate release. 18 We found that epileptic seizures terminated at 15°C or lower [19][20][21][22][23][24][25][26][27][28] and found that neuronal function deteriorated at 10°C or lower. 29,30 The threshold of low temperature for histological brain damage is not known exactly; however, irreversible damage occurred neither by continuous cooling at 5°C for 1 hour 31 nor by cooling in repeats of 30 sec at 5°C with a 1.5-min interval for 2 hours.…”
mentioning
confidence: 85%
“…The Peltier cooling system has been extensively studied for the treatment of epilepsy and has demonstrated clinical efficacy with an intraoperative application in epilepsy patients (Nomura et al, 2014). Efforts to develop clinically feasible implantable device are continuing (Dinis et al, 2017;Hata et al, 2017), and Peltier's elementbased cooling has been successfully tested in nonhuman primate (Inoue et al, 2017), as a potential clinically therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary version of this work has been described [24], but this report did not include the experiment in the cat model or the channel structure optimization in the cooling device.…”
Section: Introductionmentioning
confidence: 99%